Medium tonicity regulates expression of the Na(+)- and Cl(-)-dependent betaine transporter in Madin-Darby canine kidney cells by increasing transcription of the transporter gene. - Uchida, S (1993)
Betaine is one of the major compatible osmolytes accumulated by kidney derived Madin-Darby canine kidney cells cultured in hypertonic medium. Betaine is accumulated by Na(+)- and Cl(-)-dependent uptake from the medium. To gain insight into the mechanism by which hypertonicity evokes an increase in the Vmax of the betaine transporter in Madin-Darby canine kidney cells, we measured the relative abundance of mRNA for the transporter in cells shifted to a hypertonic medium and found parallel increases in mRNA abundance and cotransporter activity. The increase in mRNA levels preceded the increase in transporter activity slightly. Transcription of the gene for the transporter rose rapidly and to the same relative extent as mRNA abundance in cells shifted to hypertonic medium, indicating that transcription of the gene for the cotransporter plays a major role in regulating the accumulation of betaine in response to hypertonicity.